The Efficient Removal of Calcium and Magnesium Ions from Industrial Manganese Sulfate Solution through the Integrated Application of Concentrated Sulfuric Acid and Ethanol - Houyang Chen; Kaituo Wang; Xianquan Ming; Feng Zhan; Yaseen Muhammad; Yuezhou Wei; Weijian Li; Haiqing Zhan (Metals, 2021)
In the process of preparing high-purity MnSO4 from industrial MnSO4 solution, it is difficult to remove Ca2+ and Mg2+ due to their closely similar properties. In this study, thermodynamic software simulation and experimental procedures were combined to remove Ca2+ and Mg2+ from industrial MnSO4 solution to obtain high-purity MnSO4. The simulation model was applied to predict the trend of the crystallization of different ions in the solution upon the addition of H2SO4, which revealed that, at a volume ratio of H2SO4 to MnSO4 solution of more than 0.2, MnSO4 started to crystallize and precipitate. The experimental results further verified the simulation results, and the yield of MnSO4 increased with the increasing ratio of H2SO4, while the removal rate of Ca2+ and Mg2+ decreased gradually. Keeping the economic aspect in mind, the 0.3 ratio of H2SO4 was selected at which the yield of MnSO4 reached 86.44%. The removal rate of Ca2+ and Mg2+ by recrystallization reached 99.68% and 99.17% respectively after six consecutive cycles. The recrystallized sample was washed twice with anhydrous ethanol (volume ratio of ethanol to MnSO4 solution of 0.5) and dried for 6 h at 120 °C, and the purity of MnSO4·H2O reached the battery grade requirements with the final yield as high as 80.54%. This study provides important guideline information for the purification of MnSO4·H2O from industrial MnSO4 solution via a cost-effective, simple and facile approach.